Combining ability of inbred maize lines in breeding for grain quality - R. Spriazhka; V. Zhemoida; O. Makarchuk; Yu. Dmytrenko; B. Lehenkyi (Рослинництво та ґрунтознавство, 2024)
The selection of the initial material (inbred lines) and the assessment of its combining ability are key tasks in developing maize hybrids. This study aimed to select the initial material for the creation of heterotic maize hybrids with enhanced grain quality and yield. The article presented the results of research on eight lines bred by the Genetics, Breeding and Seed Production named after Prof. M.O. Zelensky at the National University of Life and Environmental Sciences of Ukraine (lines: AK157 and AK159), as well as lines obtained from the National Centre for Plant Genetic Resources of Ukraine (lines: HLG1203, VK19, VK32, AE800, AE746, UHK686, UHK37, CO255, FV243, Q170). Additionally, four tester lines carrying mutant endosperm structure genes were analysed (lines VK13 and VK69 carrying the wx mutant endosperm structure gene, and lines AE801 and AE392 carrying the ae mutant endosperm structure gene). To assess combining ability, crosses were performed using the incomplete topcross method, resulting in 24 experimental hybrids. Field trials were conducted in 2020-2021. The article presented the results of an assessment of the obtained hybrid combinations based on grain quality and yield indicators. The highest protein content during the study years was recorded in the combination VK13 × CO255; the highest starch content in VK13 × UHK686 and VK69 × FV243; the highest oil content in AE801 × AE746 and AE801 × VK19; and the highest yield in VK13 × UHK686 and AE801 × UHK37. The effects of general combining ability, constants, and variances of specific combining ability were determined for protein, starch, and oil content in the grain, as well as for yield. The findings indicated that lines VK19, AE800, CO255, FV243, Q170, VK13, and AE801 exhibited increased protein content in the grain; lines VK19, AE746, UHK686, CO255, VK13, and AE392 showed increased oil content; and lines AK157, UHK37, and AE746 demonstrated superior yield performance. Based on the results, specific inbred lines are recommended for developing maize hybrids with improved grain quality characteristics